TELAAH ATAS ENAM LARANGAN DALAM Q.S. AL-HUJURAT AYAT 11-12: ANALISIS HERMENEUTIKA HUMANISTIK - Tahir, Muhammad Suaib (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
This article explains the role of Islamic religious education teachers, one of which is in overcoming students' difficulties in reading the Koran. The role of the Islamic religious education teacher as a learning resource is intended for students to use the teacher as a figure who is able to answer all questions asked by students. Another aim of this role is to illustrate the extent to which the teacher is able to play the role as a learning resource, especially in the problem of difficulties in reading the Koran. This research uses a qualitative approach and descriptive type with a case study method. The main data sources in this research are Islamic religious education teachers and students. Meanwhile, secondary data sources are journals, e-books, printed books and so on which are directly related to this research. Data collection techniques use interviews, observation, and document examination. Meanwhile, checking the validity of the data uses credibility by extending participation, increasing persistence in research and triangulation. The results of the research findings show that the role of Islamic religious education teachers as a learning resource in overcoming students' difficulties in reading the Koran is that teachers master the material in depth, implement learning strategies and methods, are able to answer students' questions and have reference teaching materials.